CTA - A legacy of agricultural transformation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2020)
For over 35 years, CTA has effectively demonstrated how agricultural innovation can be documented, shared and scaled up to achieve significant improvements in incomes, productivity and food security.